Analisis Kebijakan terhadap Rendahnya Kinerja Pegawai Pelaksana Pengelola Data Keagamaan pada Kantor Kementerian Agama Kabupaten Hulu Sungai Utara - Halidah (JURNAL ILMIAH GEMA PERENCANA, 2023)
This article is a policy paper resulting from analyzing and identifying the low performance of employees implementing Religious Data Management at the Office of the Ministry of Religious Affairs of North Hulu Sungai Regency. The problems encountered are: (1) Religious data managers do not yet have adequate expertise, skills, and abilities; (2) The duties and functions of Religious Data Management Employees have not been carried out effectively and efficiently; and (3) Low discipline, loyalty and responsibility of Religious Data Managers in carrying out their duties. This article was written using a qualitative method with a descriptive analysis approach, to obtain relevant data according to the problem that was the object of study accompanied by secondary data analysis and direct interviews conducted in-depth (in-depth interviews). In general, this policy analysis data shows that of the 13 districts/cities in South Kalimantan Province, the North Hulu Sungai Regency Ministry of Religious Affairs Office experienced delays in data collection until the specified deadline. This results in hampered performance of religious data, both at the Provincial Regional Office level and reporting at the central level.